The lords of human kind European attitudes to the other cultures in the imperial age - Kiernan, V. G. (Victor Gordon) 1913-2009 (Critique influence change, 2015)
First published in 1969, and a major influence on a generation of historians and cultural critics, Victor Kiernan's The Lords of Human Kind reveals the full range of those responses. Drawing on a wide array of sources, including missionaries' memoirs, letters from the wives of diplomats, explorers' diaries, and the work of writers as diverse as Voltaire, Thackeray, Goldsmith, and Kipling, Kiernan presents a sweeping account of European attitudes to other peoples that emerged from the Age of Exploration, endured through the colonial era, and, with some changes, persist in today's more multicultural Europe.